Cyber Security Impact on Digitalization and Business Intelligence Big Cyber Security for Information Management: Opportunities and Challenges - Alzoubi, Haitham M.; Alshurideh, Muhammad Turki; Ghazal, Taher M. (Studies in Big Data, 2024)
X, 598 p. 34 illus., 29 illus. in color.